Hip Osteoarthritis and Osteoporosis: Clinical and Histomorphometric Considerations - Umberto Tarantino; Monica Celi; Cecilia Rao; Maurizio Feola; Irene Cerocchi; Elena Gasbarra; Amedeo Ferlosio; Augusto Orlandi (International Journal of Endocrinology)
Although an inverse relationship between osteoarthritis (OA) and osteoporosis (OP) has been shown by some studies, other reports supported their coexistence. To clarify this relationship, we analyzed the interplay between clinical and histomorphometric features. Bone mineral density (BMD) and histomorphometric structure were assessed in 80 patients of four different age-matched groups undergoing hip arthroplasty for severe OA or OP-related femoral fracture. Harris Hip Score was also performed. Surgical double osteotomy of the femoral head was performed and microscopic bone slice samples analysis was performed by using a BioQuant Osteo software. Bone volume fraction (BV/TV) was lower (P<0.01) in subjects with femoral neck fracture (20.77±4.34%) than in subjects with nonosteopenic OA (36.49±7.73%) or osteopenic OA (32.93±6.83%), whereas no difference was detected between subjects with femoral neck fractures and those with combined OA and OP (20.71±5.23%). Worse Harris Hip Score was found in those patients with the lowest BMD and BV/TV values. Our data support recent evidences indicating the possibility of impaired bone volume fraction in OA patients, with a high risk of developing OP, likely for their decreased mobility. Further studies are needed in order to investigate biomolecular pathway and/or growth factors involved in bone volume impairment in OA patients.